Fourier transformation and response functions - Gunnarsson, Olle; Haverkort, Maurits W. (Arxiv, 2010)
We improve on Fourier transforms (FT) between imaginary time $τ$ and imaginary frequency $ω_n$ used in certain quantum cluster approaches using the Hirsch-Fye method. The asymptotic behavior of the electron Green's function can be improved by using a "sumrule" boundary condition for a spline. For response functions a two-dimensional FT of a singular function is required. We show how this can be done efficiently by splitting off a one-dimensional part containing the singularity and by performing a semi-analytical FT for the remaining more innocent two-dimensional part.